Prophylactic analgesic effect of paracetamol and ibuprofen in the extraction of teeth in children - Mery Cecilia Paccini Torres; Rafael Morales Vadillo (Kiru)
Objective: To evaluate the prophylactic analgesic effect of paracetamol and ibuprofen administered before the extraction of deciduous teeth in children. Materials and methods: Sixty children of 6 to 8 years of age were evaluated and attended the Dental Center of the Faculty of Dentistry of the University of San Martín de Porres, which were distributed in three groups, each of 20 children: group paracetamol, ibuprofen group and the control group. In the first two, the corresponding drug was administered orally 30 minutes before surgery (paracetamol 15 mg / kg or Ibuprofen 10 mg / kg). The following variables were evaluated: presence of pain, time of presence of pain, intensity of pain, and time elapsed for rescue analgesia. Results: Significant differences were found in the presence of pain variable and in the time of presence of pain among the 3 groups. There was no significance between the variables studied between the two groups with drugs. Conclusions: Analgesic prophylaxis is an effective alternative to conventional post-surgical pharmacological treatment. Ibuprofen and Paracetamol are drugs with similar efficacy for this purpose, despite presenting different pharmacological action.